Solubilities of trace copper and lead species and the complexing capacity of river water in the Linggi River Basin - Tan, Wee Tee; Tan, Gaik See; Nather Khan, I. S. A. (Elsevier, 1988)
Chemical forms of copper and lead in river water of the Linggi River Basin have been fractionated into ASV labile, moderately labile, slowly labile, and inert metal species, based on a previously proposed scheme. Free (hydrated) metal ions were identified by a potentiometric method using an ion selective electrode. Speciation results showed that the soluble copper and lead species occurred mainly in the moderately labile and slowly labile fractions. The speciation results are primarily interpreted in terms of organic interaction due to agricultural based and light industries, and urban discharges. The measured metal complexing capacity (MCC) of the samples reveals consistency of the results with the nature of the discharge. MCC correlates reasonably well with the value from the permanganate test on the river water. In general, the speciation pattern was found to be consistent with the findings of other workers